2016
DOI: 10.1159/000445777
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Endoscopic Biliary Drainage May Negatively Impact Survival Following Pancreatoduodenectomy for Ampullary Cancer

Abstract: Background/Aims: Ampullary carcinoma is a rare tumour with a high resectability rate. There is an increasing body of evidence indicating not only tumour-related factors, but also jaundice influence survival following curative resection. Several modalities for preoperative biliary drainage are available; however, routine preoperative endoscopic biliary drainage (PEBD) is not recommended. There is no sufficient data regarding the impact of PEBD on long-term outcomes. The aim of our study was to identify predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated that CA19-9 and bilirubin are independent prognostic factors in present study despite different cut-off values ( 5 , 8 ). Additionally, to the best of our knowledge, there is no existing evidence suggesting that preoperative biliary stenting has an influence on operative mortality or subsequent survival following a pancreaticoduodenectomy ( 53 55 ), an adjusted cut-off value of bilirubin to 190 µmol/l (elevated the best cut-off via maximally selected log-rank statistics) was used for the survival benefit of preoperative biliary drainge. Sex showed no significance in univariate survival analysis of median survival time 42 months for males and >60 months for females (P=0.7746).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that CA19-9 and bilirubin are independent prognostic factors in present study despite different cut-off values ( 5 , 8 ). Additionally, to the best of our knowledge, there is no existing evidence suggesting that preoperative biliary stenting has an influence on operative mortality or subsequent survival following a pancreaticoduodenectomy ( 53 55 ), an adjusted cut-off value of bilirubin to 190 µmol/l (elevated the best cut-off via maximally selected log-rank statistics) was used for the survival benefit of preoperative biliary drainge. Sex showed no significance in univariate survival analysis of median survival time 42 months for males and >60 months for females (P=0.7746).…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 ESGE Guideline recommends against routine preoperative biliary drainage in patients with malignant extrahepatic biliary obstruction [110]; A recent systematic review, published after that Guideline and including 32 studies, confirmed that refraining from preoperative drainage before pancreaticoduodenectomy may be the best management for jaundice in patients with resectable pancreatic head cancer [129]. If we focus on studies including only patients with resectable adenocarcinoma, a retrospective series including 64 patients concluded that preoperative drainage was an independent negative predictive factor influencing survival (drainage vs. no drainage, 25.3 months vs. 112.9 months, P < 0.001) [130]. Similarly, a French retrospective series including 135 patients with nonductal periampullary tumors identified preoperative drainage as a predictive factor for recurrence [131].…”
Section: Recommendationmentioning
confidence: 96%
“…Although the meta-analyses were limited by the characteristics of the original studies, including selection bias, the use of the percutaneous or the endoscopic route for PBD, and the inclusion in some studies of patients with proximal biliary obstruction, they represent the best available evidence. Of note, two retro-spective studies that compared PBD vs. no PBD in a total of 170 patients reported an independent association between endoscopic PBD and shorter patient survival [17,18].…”
Section: Preoperative Biliary Drainagementioning
confidence: 99%